Structural and computational studies on the nature of Au(iii) ...Q interactions - Speirs, Daniel J (My University, 2018)
Pincer ligands derived from the reaction of one mole equivalent of pyridine-2,6-dicarbonyl dichloride with 2 moles of 2,4,6-trimethylaniline or cyclohexanamine were synthesized and characterized by 1H NMR, 13C NMR, FTIR, high resolution MS, UV-visible spectroscopy and single crystal X-ray diffraction. A dynamic NMR analysis was performed on the novel bis(cyclohexylamide) derivative to delineate its conformational preferences and to demonstrate that this class of ligands is pre-organized for metal ion chelation. Pd(II) and Au(III) derivatives of the bis(mesitylamide) ligand system were then synthesized and reacted with quinoline as a co-ligand, which gave four-coordinate derivatives with the quinoline bound to the metal ion within the pocket of the pincer chelate. These novel metal chelates were characterized by 1H NMR, 13C NMR, FTIR, high resolution MS, UV-visible spectroscopy and single crystal X-ray diffraction. The Au(III), Pt(II), and Pd(II) chelates of the pincer ligands were used as experimental and in silico receptors for the binding of quinoline co-ligands bearing a range of substituent atoms at ring-position 8. This permitted investigation of the near-axial nonbonded interaction of the substituent atom at ring-position 8 with the metal ion. Density functional theory (DFT) calculations and atoms in molecules (AIM) analyses were performed on both the metal-free ligands and on a series of theoretical, quinoline-containing chelates of Pd(II), Pt(II), and Au(III). The atom at ring-position 8 on the quinoline (the Q atom) was systematically varied (H, F, Cl, Br, I) to delineate the electronic properties of the MQ axial interaction. The DFT basis sets used were SDD, DGDZVP, 6-311G(d,p), and SARC-ZORA in conjunction with the HSEH1PBE functional. The computational analysis suggested that partially 5-coordinate Au(III) species can, in principle, form in a suitably constrained system such as that designed herein. A partial, axial dative covalent bond with substantial ionic character may be formed with Au(III) because electron density is forced from the p- and s-orbitals of the interacting atom (Q) into the vacant 6pz atomic orbital of the Au(III) ion. This study therefore challenges the long-held notion that Au(III) complexes will always be square planar.
Submitted in the fulfilment of the requirements for the degree of Master of Science. School of chemistry February 2018